Assessing the Challenges and Opportunities for Implementing New and Renewable Energy Policy in Indonesia: A Qualitative Study - Asep Nurjaman Nurjaman; Vina Salviana Darvina Soedarwo; Djoko Sigit Sayogo; Rachmad K Dwi Susilo (Universitas Muhammadiyah Tangerang, 2024)
The purposes of the study are to examine the challenges and opportunities for Implementing New and Renewable Energy Policy in Indonesia. In this qualitative study, the data were analyze by using Regulatory Impact Assessment (RIA) and SWOT analysis to assess the challenges and opportunities of NRE policy and technology in Indonesia. Our findings suggest that despite the abundance of NRE resources, the country needs to reform its policies to support NRE development better and increase investment in NRE infrastructure. Furthermore, inadequate technological research and development significantly challenge NRE adoption. While the Government should be more active in fostering NRE development, we advise universities to play a critical role in developing NRE technology. Furthermore, solar energy is the most appropriate choice to be implemented in Indonesia because of its position at the equator where solar energy is abundant. This study provides valuable insights into energy policy in Indonesia and contributes to the global efforts towards achieving a sustainable future.Tujuan dari studi ini adalah untuk mengkaji tantangan dan peluang Penerapan Kebijakan Energi Baru dan Terbarukan di Indonesia. Dalam studi kualitatif ini, data dianalisis dengan menggunakan Regulatory Impact Assessment (RIA) dan analisis SWOT untuk menilai tantangan dan peluang kebijakan dan teknologi EBT di Indonesia. Temuan kami menunjukkan bahwa meskipun sumber daya EBT berlimpah, negara ini perlu mereformasi kebijakannya untuk mendukung pengembangan EBT dengan lebih baik dan meningkatkan investasi pada infrastruktur EBT. Selain itu, kurangnya penelitian dan pengembangan teknologi menjadi tantangan besar dalam penerapan EBT. Meskipun Pemerintah harus lebih aktif dalam mendorong pengembangan EBT, kami menyarankan perguruan tinggi untuk memainkan peran penting dalam pengembangan teknologi EBT. Lebih lanjut, energi surya menjadi pilihan yang paling tepat untuk diterapkan di Indonesia karena posisinya yang berada di garis khatulistiwa dimana energi surya melimpah. Studi ini memberikan wawasan berharga mengenai kebijakan energi di Indonesia dan berkontribusi terhadap upaya global untuk mencapai masa depan yang berkelanjutan.